1970
DOI: 10.3126/on.v3i1.332
|View full text |Cite
|
Sign up to set email alerts
|

General Biology of Freshwater Prawn, <i>Macrobrachium lamarrei</i> (H. Milne-Edwards) of Biratnagar, Nepal

Abstract: Macrobrachium lamarrei (H. Milne-Edward) is commonly known as “kuncho river prawn,” occurring in freshwater ponds and rivers of Biratnagar, Nepal. They are nocturnal species feed voraciously on planktonic organisms, algae, muscles pieces of their own kind or fish etc. M. lamarrei is a medium-sized prawn ranging from 75-80 mm in length rostrum bears 7-9 teeth dorsally and 5-8 ventrally. The estimation of fecundity was done following egg counting method from March, 2004 to February, 2005. The mean fecundity rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 3 publications
(2 reference statements)
5
19
1
Order By: Relevance
“…Da Silva et al (2004) reported the highest number of eggs (2193) for M. amazonicum. The same trend was found for M. lamarrei (Sharma & Subba 2005). The same trend was found for M. lamarrei (Sharma & Subba 2005).…”
Section: Fecundity Incubation Period and Hatching Ratesupporting
confidence: 83%
“…Da Silva et al (2004) reported the highest number of eggs (2193) for M. amazonicum. The same trend was found for M. lamarrei (Sharma & Subba 2005). The same trend was found for M. lamarrei (Sharma & Subba 2005).…”
Section: Fecundity Incubation Period and Hatching Ratesupporting
confidence: 83%
“…According to Lewis et al (1966) M. carcinus is a prawn that ingests high percentage of detritus (77%) especially in the juvenile prawns, which is not evident in this study. Our results indicate that M. carcinus is omnivorous, but with an important carnivorous component, similar to that found in other species of Macrobrachium, such as M. amazonicum (Odinetz-Collart 1988), M. lamarrei (Sharma and Subba 2005), M. acanthurus (Albertoni et al 2003) and M. vollenhovenii . Lewis et al (1966) reported algae, detritus, animal and vegetable fragments in the stomach of M. carcinus; plant material was represented by leaves and stems of aquatic plants and seeds of various types; while animal items were represented by aquatic insects, fish, mollusks and other crustaceans.…”
Section: Discussionsupporting
confidence: 61%
“…It inhabits freshwater, brackish water and marine ecosystems. Sharma and Subba (2005) cited that prawn belonging to the Family Paleomonidae has marine origin and has acquired freshwater habitat by immigration from the sea to the interior of land through rivers. The prawn species such as "udang" "kinod" and "tangad" eat all types of food living or dead: consume algae, planktonic organisms, small muscle pieces of their own kind or fish [21].…”
Section: Indigenous Speciesmentioning
confidence: 99%